Monkeypox: A Comprehensive Analysis of Emerging Epidemiological Trends, Pathogenesis, and Advanced Therapeutic Interventions - Saikia, Prasurjya; Kemisetti, Durgaprasad; Rath, Amrit Kumar; Mishra, Sruti Ranjan (Coronaviruses, 2025)
Monkeypox has become a major worldwide health issue, which has brought attention to the necessity of having a thorough understanding of this zoonotic virus. An extensive examination of the monkeypox virus's taxonomy, morphology, replication cycle, transmission, clinical symptoms, and treatment options is given in this article. The review also addresses the possibility that, given the growing interconnection of human populations and the drop in smallpox vaccination rates, the monkeypox virus will take over the ecological niche once occupied by the smallpox virus.
Keywords: prevention